5 - An Alternative Theoretical Model for Economic Reforms in Africa - Obiora, Kingsley I. (Africa Development, 2007)
This paper offers an alternative model for economic reforms in Africa. It proposes that Africa can still get on the pathway of sustained economic growth if economic reforms can focus on a key variable, namely, the price of non-tradables. Prices of non-tradables are generally less in Africa than in advanced economies, and the typical basket of goods for many Africans will contain more non-tradables, while the reverse is the case in advanced economies. Working through its effect on the real exchange rate and given some plausible assumptions, this paper demonstrates that economic reforms which reduce the price of non-tradables in Africa vis-à-vis the price of non-tradables in advanced economies can lead to real exchange rate depreciation, a rise in net exports, an avoidance of the “Dutch Disease” syndrome and a rise in per capita income. The paper concludes that any economic reforms that either skew consumption in Africa in favour of non- tradables vis-à-vis tradables or that reduce the price of non-tradables in Africa vis-à-vis non-tradables in advanced economies is likely to be welfare-improving.